Alcohol Consumption and Risk of Common Autoimmune Inflammatory Diseases—Evidence From a Large-Scale Genetic Analysis Totaling 1 Million Individuals - Jiang, Xia; Zhu, Zhaozhong; Manouchehrinia, Ali; Olsson, Tomas; Alfredsson, Lars; Kockum, Ingrid (Frontiers in Genetics, 2021)
Purpose: Observational studies have suggested a protective effect of alcohol intake with autoimmune disorders, which was not supported by Mendelian randomization (MR) analyses that used only a few (< 20) instrumental variables. Methods: We systemically interrogated a putative causal relationship between alcohol consumption and four common autoimmune disorders, using summary-level data from the largest GWAS conducted on inflammatory bowel disease (IBD), rheumatoid arthritis (RA), multiple sclerosis (MS) and systemic lupus erythematosus (SLE). We quantified the genetic correlation to understand a shared similarity. We constructed a strong instrument using 99 genetic variants associated with drinks/week and applied several two-sample MR methods. We additionally incorporated excessive drinking as reflected by alcohol use disorder identification test score. Results: We observed negatively shared genetic basis between alcohol intake and autoimmune disorders although none was significant (rg -0.07- -0.02). For most disorders, genetically predicted alcohol consumption was associated with a slightly (10-25%) decreased risk of onset, yet these associations were not significant. Meta-analyzing across RA, MS and IBD, the three Th1-related disorders, yielded to a marginally significantly reduced effect (OR=0.70 (0.51-0.95), P=0.02). Excessive drinking did not appear to reduce the risk of autoimmune disorders. Conclusions: With its greatly augmented sample size and substantially improved statistical power, our MR does not convincingly support a beneficial role of alcohol consumption in each individual autoimmune disorder. Future studies may be designed to replicate our findings and to understand a causal impact on disease prognosis.